Population genetic characteristics for populations on the Shandong Peninsula revealed by autosomal STR. (17th February 2021) - Zhou, Yijun; Huang, Lei; Liu, Haidong; Liu, Mengnan; Fan, Guangyao
Abstract: The Shandong Peninsula is the largest peninsula in China and has played a vital part in Chinese civilisation. The ancient independent Laizi kingdom was located on the Shandong peninsula. While large demographic changes have happened at this peninsula throughout history, the genetic landscape of modern populations on this peninsula has never been clarified. The aims of our study were to investigate population genetic characteristics of the populations on the Shandong peninsula and to reveal their genetic affinities with other populations around the world. Allele frequencies, Hardy–Weinberg equilibrium, and forensic parameters of 15 autosomal STRs in the AmpF l STR ® Identifiler system were obtained from the studied populations with 2441 individuals in total. Allele frequencies were used to reveal the phylogenetic relationships among 287 worldwide populations. The combined power of discrimination (CPD) and the combined power of exclusion (CPE) in the whole of the Han population on the Shandong Peninsula were 0.999999999999999983 and 0.999998155, respectively. The 15 autosomal loci were polymorphic and informative among our studied populations. Genetic homogeneities were revealed between the modern populations on the Shandong Peninsula and Han nationalities from Northeastern China as well as East China.